Literature Review the Effect of Technology, Environment and Organizational Strategy on Organizational Structure - Ahmad Munawar, Niknik (Dinasti Publisher, 2021)
Organizational Development is a systematic and planned approach to improve organizational effectiveness and help solve problems. Some of the things included in Change Management are Individuals, Work Teams, Organizational cooperation/cooperation, excessive decentralization and lack of speed of communication which affects the efficiency of operations at all levels. Organizational strategic change is a new influence on the evolution of organizational development. Organizational structure and technology, organizational strategy and the increasingly complex social environment encourage organizational change to increase. An organization will experience a development if the organization can be declared successful when it develops in a positive direction, so that employees who join the organization can achieve their goals. The development of the organizational structure requires adjustments to the system within the organization in order to keep up with the changing times. The development of an organization can also be used as a scale for the organization, whether the organization remains active and protects the employees in the organization as well as in the face of the times. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research.